ETRAN—R Extension Package for Eye Tracking Results Analysis. (August 2015) - Zhegallo, Alexander V.; Marmalyuk, Pavel A.
Novel open source R extension package for general-purpose eye tracking results analysis proposed. Now supported features are data loading from SMI eye trackers, different methods of fixations detection, various imaging techniques for raw data, and detected fixations (time sequence, scanpath, heatmap, and dynamic visualization). The modular structure of the package and a detailed description of each function provide a convenient way to further extend the functionality. Effective use of package requires knowledge of R programming language and environment.